Septoplasty: defining a desirable clinical outcome according to baseline symptom scores - Haye, Rolf; Døsen, Liv Kari; TarAngen, Magnus; Gay, Caryl; Pripp, Are Hugo; Shiryaeva, Olga (Frontiers in Surgery, 2025)
ObjectiveThe results of septoplasty are usually reported as statistically significant improvements in baseline scores, but these may be difficult to interpret clinically. A measure called the desirable clinically important difference (DCID) has been developed to serve as a guideline to assist in clinically interpreting improvement in scores. So far, DCID has only been calculated for whole cohorts. As individual patients have different baseline and improvement scores, such measures are not helpful to individuals. Our aim was to establish a DCID according to baseline scores, which should help assess individual results.MethodsPatients (n = 934) rated their nasal obstruction using a visual analog scale (VAS) preoperatively and 6 months postoperatively. A global rating of outcome (categorized as completely, much, or somewhat improved, unchanged, or worse) served as the anchor for postoperative evaluation. The improvement in VAS score corresponding to the “much improved” rating was defined as the borderline value between “much” and “somewhat improved.” Receiver operating characteristics were used to establish this borderline value. The DCID is the difference between the borderline and baseline VAS scores. The relative DCID is calculated by dividing the numeric DCID by the baseline VAS score. The cohort was divided into three subgroups (moderate, severe, very severe) according to preoperative severity of nasal obstruction (VAS score) for assessing the relation between DCID and baseline obstruction severity.ResultsThe DCID increased with increasing severity of baseline nasal obstruction: 27.5 (moderate), 44.5 (severe), and 56.0 (very severe), as did the relative DCID: 49.6% (moderate), 56.8% (severe), and 61.3% (very severe).ConclusionThe relative DCID can be a guide for assessing improvement following septoplasty according to baseline scores of nasal obstruction and for planning surgery. A 49% improvement from baseline is indicative of clinical success for a patient with moderately obstructed nasal breathing, whereas patients with very severe obstruction require a 61% improvement.